Exclusive breastfeeding intention among pregnant women and associated variables: a cross-sectional study in a Brazilian community - Silva, Lorena Fonseca [UNESP]; Cortellazzi, Karine Laura; de Melo, Letícia Santos Alves [UNESP]; da Silva, Silvio Rocha Corrêa [UNESP]; Rosell, Fernanda L. [UNESP]; Valsecki, Aylton [UNESP]; da Silva Tagliaferro, Elaine Pereira [UNESP] (FapUNIFESP (SciELO), 2024)
Objective: To investigate exclusive breastfeeding (EBF) intention and associated variables among women in the third trimester of pregnancy. Methods: The data were collected with a questionnaire for the pregnant women (n=653), from December/2018 to November/2019. They answered the Infant Feeding Intentions (IFI) scale, translated and adapted to Brazilian Portuguese, and a questionnaire on sociodemographic, biological, family, pregnancy, breastfeeding, health care, and habits variables. Descriptive statistics and multiple logistic regression analyses were performed with a 5% significance level, following a multilevel hierarchical model that estimated the association between the dependent and independent variables. The outcome EBF intention measured by the IFI score was dichotomized by the median (<16 or =16). Results: Mean }standard deviation score for the IFI scale was 14.4 }2.6 (score 0: very strong intention to not breastfeed at all; score 16: very strong EBF intention up to six months). The results from the regression analysis showed that pregnant women who had no intention to bottle feed (OR=4.33; 95%CI 2.79-6.72) or did not know (OR=1.85; 95%CI 1.21-2.82), those who planned the pregnancy (OR=1.52; 95%CI 1.09-2.12), those who believed they would have help to care for the baby (OR=3.60; 95%CI 1.51-8.56) or did not know (OR=3.97; 95%CI 1.26-12.51), and those who reported knowing the World Health Organization recommendations on breastfeeding (OR=1.73; 95%CI 1.13-2.64) were more likely to show a very strong EBF intention. Conclusions: Pregnant women in the third trimester of pregnancy presented a strong EBF intention. The higher EBF intention score was significantly associated with the structural, setting, and individual determinants.
Keywords: Breastfeeding; Intention; Pregnant women